Strategi Guru dalam Pendidikan Akhlak dan Penanaman Nilai-Nilai Aqidah Siswa melalui Pembiasaan Budaya Madrasah - Maulani, Kharisma (Maliki Interdisciplinary Journal, 2025)
Mu’allim/Mu’allimah, Teachers (educators) are parents who are at the school/madrasah. It can be said that the teacher is the second parent, which of course means that a teacher has full trust and responsibility for the morals, beliefs, worship and knowledge that a student acquires. Just like the students’ biological parents who educate and teach them from childhood. A teacher is obliged to pay attention to students from all aspects, both worldly and spiritual. Teachers must have strategies (methods), goals and student achievements in applying the values of Islamic religious education which are guided by the Al-Qur’an and Hadith which contain the cultivation of Aqidah, the practice of worship, having good morals and gaining useful and blessed knowledge. The cultivation of good things that must be instilled in students from childhood, especially through formal education (Elementary School-COLLEGE)-(Madrasah Ibtida’iyah-COLLEGE).